Mechanisms of liver disease in patients infected with HIV - Matthew B Kaspar; Richard K Sterling (BMJ Open Gastroenterology)
Objective To describe the various mechanisms of liver disease in patients with HIV infection, and to link these mechanisms to disease states which may utilise them.Background Non-AIDS causes of morbidity and mortality are becoming increasingly common in patients chronically infected with HIV. In particular, liver-related diseases have risen to become one of the leading causes of non-AIDS-related death. A thorough understanding of the mechanisms driving the development of liver disease in these patients is essential when evaluating and caring for these patients.Methods The literature regarding mechanisms of liver disease by which different disease entities may cause hepatic injury and fibrosis was reviewed and synthesised.Results A number of discrete mechanisms of injury were identified, to include: oxidative stress, mitochondrial injury, lipotoxicity, immune-mediated injury, cytotoxicity, toxic metabolite accumulation, gut microbial translocation, systemic inflammation, senescence and nodular regenerative hyperplasia. Disease states may use any number of these mechanisms to exert their effect on the liver.Conclusions The mechanisms by which liver injury may occur in patients with HIV infection are numerous. Most disease states use multiple mechanisms to cause hepatic injury and fibrosis.